Tom Lea’s Toros Bravos - Margo, Adair (RITUR - Revista Iberoamericana de Turismo, 2019)
In the world of art and literature, Tom Lea holds a remarkable place. Rarely is an artist who looks at the world to record it in drawing or painting, also able to listen to the world to describe it in words. Tom Lea did both. He mastered the tools of an artist, whether with a piece of charcoal, pen or brush in his hand. He also mastered the written word, teaching himself to say exactly what he meant with vivid expression. These two different talents came together in his first illustrated novel, The Brave Bulls, published in 1948. Placed on the New York Times best seller list and translated into ten foreign editions, the book introduced its protagonist, Luis Bello, and his life as a Mexican matador to the rest of the world. The novel was turned into a Hollywood movie starring Mel Ferrer and the Czechoslovakian-born Mexican film actress Miroslava, which premiered at the Plaza Theater in El Paso, Texas in 1951.